Heavy metals in the air and their adverse effects on human being health; The 7th International Forum on Strategic Technology (IFOST-2012), September 18-21, 2012, Tomsk - Osipova N. A. Nina Aleksandrovna; Yankovich E. P. Elena Petrovna; Yazikov Y. G. Yegor (Egor) Grigoryevich; Talovskaya A. V. Anna Valerievna (2012, 2012)
Title screen